Optimization of reparative osteogenesis with using of calcium phosphate osteoplastic materials (literature review) - Korenkov, Olexiy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
<span style="font-size: 14.0pt; line-height: 115%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The analysis of domestic and foreign scientific sources on the possibilities of calcium phosphate osteoplastic materials for optimization of the reparative osteogenesis was done. It was found that different kinds of texture and geometric shapes of calcium phosphate osteoplastic materials make it possible to fill the defects of various configurations. Impregnation of granules, blocks and cylinders with hydrophilic surface with sterile physiological saline, autologous blood, blood products, bone marrow cells provide such texture of the material which might be easily modeled with a scalpel according to the shape of the defect, and thus it is useful in the surgical field. Synthetic nature of calcium phosphate materials ensures their safety in clinical practice, preventing the risk of infections, the occurrence of immune and genetic incompatibility, rejection reaction, suppuration, and allergic reactions. Xenografs of bovine bones also demonstrate safety concerning allergic reactions, bovine spongiform encephalopathy and other infections because of deproteinisation and high temperature processing (above 800 ºC) in time of their producing. Above all calcium-phosphate osteoplastic materials have osteoconductive, osteostimulative and secondary osteoinductive features, and impregnation of some implants with antibiotic allows to create on the site of implantation anti-bacterial and anti-inflammatory effects. Osteocondution caused by macro-, micropores and rough structure of osteoplastic materials, osteostimulation caused by their ability to adsorb growth factors on their surface and calcium ions from implants, and the secondary osteoinduction caused by bone morphogenetic proteins which absorb from tissue environment of the bone defect and blood on their surface or comprise to the implant. It was found that calcium phosphate osteoplastic materials are able to optimize angiogenesis, adhesion, proliferation of osteogenic cells and their differentiation into osteoblasts in the area of the defect and, consequently, newly development of bone tissue directly on the surface and in the cavities of the implant. It was shown that initially granulation tissue with blood vessels or osteoid, and after that trabecular mesh of woven bone tissue with a gradual formation of mature lamellar bone to be formed. Due to the phenomenon of precipitation and association with newly formed bone tissue of dissolved crystals of implanted calcium phosphate materials and activity of osteoblasts it is subjected to mineralization and remodeling resulting in the formation of bone tissue with architectonics which according to the law of Julius Wolff meets concrete functional load acting on bone. Simultaneously with bone formation due to the activity of osteoclasts and macrophages calcium phosphate osteoplastic materials are subjected to gradual resorption with speed ranging from some months to 11 years. The latter depends on many factors among which there are physical and chemical characteristics of material, size and structure of pores, geometrical shape, architectonics of the surface, impregnating substances before implantation, technical nuances of producing as well as type of bone which it implanted in. Different expressiveness of the above mentioned properties of implants must be considered in case of application in each clinical situation.